The influence of perceived formative assessment on the learning autonomy of medical students: the chain mediating role of psychological empowerment and positive academic emotions - Jiali Wang; Guorun Zhou; Juntang Guo; Xiaodong Sun; Lin Sun (Frontiers Media S.A., 2024)
IntroductionMedical students' autonomous learning is a cornerstone of their educational journey. Formative assessment is defined as a process to enhance learning and improve academic performance, and the key to the effectiveness of formative assessment is the students' perceptions of it. The present study investigates the impacts of perceived formative assessment on the learning autonomy of medical students, explores the chain mediating role of psychological empowerment and positive academic emotions, and offers strategies for facilitating medical students' autonomous learning.MethodsA cross-sectional investigation was conducted using a convenience sampling method involving 713 medical students (mean age 19.72 ± 1.18 years; 207 male and 506 female students; the proportion of participants is 93.69%) in Shandong Second Medical University. Perceived formative assessment was performed using a self-designed questionnaire of Perceived Formative Evaluation for Medical Students, learning autonomy using the Autonomy in Learning Rating Scale for College Students, positive academic emotions using the General Academic Emotion Questionnaire for College Students, and psychological empowerment of medical students using the Chinese version of Psychological Empowerment Scale (PES). The data were analyzed using descriptive statistics, Pearson's correlation, multiple regression, and mediation analysis using the SPSS26.0 program and PROCESS3.1.ResultsPerceived formative assessment significantly predicted learning autonomy (β = 0.06, p < 0.05). It also positively predicted psychological empowerment (β = 0.20, p < 0.001), and psychological empowerment positively predicted the learning autonomy of medical students (β = 0.36, p < 0.001). Psychological empowerment also positively predicted positive academic emotions (β = 0.64, p < 0.001), and positive academic emotions positively predicted learning autonomy (β = 0.44, p < 0.001). The direct effect value of perceived formative assessment on learning autonomy was 0.18, while the total indirect effect was 0.43. The mediation effect of psychological empowerment on the relationship between perceived formative assessment and learning autonomy was 0.22, and the chain mediation effect of psychological empowerment and positive academic emotions was 0.18, accounting for 30%, 70%, 36%, and 30% of the total effect, respectively.ConclusionPerceived formative assessment directly enhances medical students' learning autonomy. This relationship is partially mediated by psychological empowerment and positive academic emotions. The results suggest that formative evaluation boosts psychological empowerment, which fosters positive academic emotions and further promotes learning autonomy.